Literasi Terapan melalui Keterampilan Membuat Batik Sibhori di SD-SMP Muhammadiyah Bersama Forum PUSPA Hamidah Kota Tanjungpinang: Empowering Applied Literacy through Shibori Batik Training at Muhammadiyah School with Forum PUSPA Hamidah in Tanjungpinang - Diah Siti Utari; Nevyrasari, Merin; Susanti, Iwa; Arfa, Desmayeti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Skills are among the most important competencies that students must acquire to face the challenges of the twenty-first century. Applied literacy is a strategic approach to developing students' creativity, collaboration, motor, and cognitive skills. Forum PUSPA Hamidah of Tanjungpinang, a community dedicated to women's empowerment and child protection, has launched a Shibori Batik training program at Muhammadiyah School in Tanjungpinang. This initiative is a form of collaboration between the community and the school to support implementing literacy programs in educational settings. Seventy-one students actively participated in the training, which was intended to be enjoyable and meaningful, through lectures, demonstrations, and hands-on practice. Community facilitators and school teachers guided participants as they folded, tied, and dyed fabric to create unique Shibori Batik patterns. The results showed increased enthusiasm, improved teamwork, and the students' successful production of Shibori Batik fabric as a creative output. This activity improved cultural arts learning by demonstrating how community involvement can broaden learning opportunities in contextual, participatory, and relevant ways. This initiative is expected to be a best-practice model for developing applied literacy through long-term cross-sector partnerships between communities and schools. This culturally-based applied literacy innovation type is widely replicable at the primary and secondary levels.